Development of phase change materials based microencapsulated technology for buildings: A review - Tyagi, V.V.; Kaushik, S.C.; Tyagi, S.K.; Akiyama, T. (Renewable & sustainable energy reviews, 2011)
Thermal energy storage (TES) systems using phase change material (PCM) have been recognized as one of the most advanced energy technologies in enhancing the energy efficiency and sustainability of buildings. Now the research is focus on suitable method to incorporate PCMs with building. There are several methods to use phase change materials (PCMs) in thermal energy storage (TES) for different applications. Microencapsulation is one of the well known and advanced technologies for better utilization of PCMs with building parts, such as, wall, roof and floor besides, within the building materials. Phase change materials based microencapsulation for latent heat thermal storage (LHTS) systems for building application offers a challenging option to be employed as effective thermal energy storage and a retrieval device. Since the particular interest in using microencapsulation PCMs for concrete and wall/wallboards, the specific research efforts on both subjects are reviewed separately. This paper presents an overview of the previous research work on microencapsulation technology for thermal energy storage incorporating the phase change materials (PCMs) in the building applications, along with few useful conclusive remarks concluded from the available literature.